Supersymmetric and shape-invariant generalization for nonresonant and intensity-dependent Jaynes-Cummings systems - Aleixo, ANF; Balantekin, A. B.; Ribeiro, MAC (Iop Publishing Ltd, 2001)
A class of shape-invariant bound-state problems which represent transitions in a two-level system introduced earlier are generalized to include arbitrary energy splittings between the two levels as well as intensity-dependent interactions. We show that the coupled-channel Hamiltonians obtained correspond to the generalizations of the nonresonant and intensity-dependent Jaynes-Cummings Hamiltonians, widely used in quantized theories of lasers. In this general context, we determine the eigenstates, eigenvalues, the time evolution matrix and the population inversion matrix factor.